A facile and scalable route to nano-crystallized kesterite Cu2ZnSnS4 fibers via electrospinning/sulfurization. (January 2015) - Song, Yuanqiang; Liu, Aifang; Mu, Chunhong; Huo, Weirong; Lv, Weiqiang; He, Weidong
Graphical abstract: Detailed characterization of the microstructure and its properties have been done on the nanocrystallized CZTS nanofibers fabricated via electrospinning following sulfurization. The fiber growth mechanism is proposed to explain the spontaneous reaction and crystallization of CZTS, as confirmed by the thermodynamic calculations. Abstract: In this work, we report facile route to quaternary kesterite Cu2 ZnSnS4 (CZTS) microfibers through electrospinning method. Precursor fibers are electrospun from the solution composed of Cu(CH3 COO)2, Zn(CH3 COO)2, and SnCl4 as the solutes, ethylene glycol methyl ether as the solvent, and polyvinylpyrrolidone (PVP) as the plasticizer. CZTS fibers are obtained after annealing at 773 K for 40 min in a sulfur ambient. Characterization including scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Raman spectra, confirm the formation of single-phased, well-crystallized CZTS fibers, with a band gap of about 1.48 eV estimated from the optical absorption curve. In addition, the fiber growth mechanism is proposed to explain the spontaneous reaction and crystallization of CZTS, as confirmed by the thermodynamic calculations.